Tight junction channels claudin‐10b and claudin‐15: Functional mapping of pore‐lining residues. Issue 1 (1st June 2022) - Hempel, Caroline; Rosenthal, Rita; Fromm, Anja; Krug, Susanne M.; Fromm, Michael; Günzel, Dorothee; Piontek, Jörg
Abstract: Although functional and structural models for paracellular channels formed by claudins have been reported, mechanisms regulating charge and size selectivity of these channels are unknown in detail. Here, claudin‐15 and claudin‐10b cation channels showing high‐sequence similarity but differing channel properties were analyzed. Mutants of pore‐lining residues were expressed in MDCK‐C7 cells. In claudin‐15, proposed ion interaction sites (D55 and E64) conserved between both claudins were neutralized. D55N and E64Q substitutions decreased ion permeabilities, and D55N/E64Q had partly additive effects. D55N increased cation dehydration capability and decreased pore diameter. Additionally, residues differing between claudin‐15 and ‐10b close to pore center were analyzed. Claudin‐10b–mimicking W63K affected neither assembly nor function of claudin‐15 channels. In contrast, in claudin‐10b, corresponding (claudin‐15b‐mimicking) K64W and K64M substitutions disturbed integration into tight junction and slightly altered relative permeabilities for differently sized monovalent cations. Removal of claudin‐10b–specific negative charge (D36A substitution) was without effect. The data suggest that a common tetra‐aspartate ring (D55/D56) in pore center of claudin‐15/‐10b channels directly attracts cations, while E64/D65 may be at least partly shielded by W63/K64. Charge at position W63/K64 affects assembly and properties for claudin‐10b but not for claudin‐15 channels. Our findings add to the mechanistic understanding of the determinants of paracellular cation permeability. Abstract : To investigate assembly and function of paracellular cation channels, mutants of pore‐lining residues of claudin‐10b and ‐15 (high sequence similarity but different properties) were analyzed in MDCK‐C7 cells. In claudin‐15, D55N decreased ion permeability but increased cation dehydration capability. Claudin‐10b‐mimicking W63K had no effect in claudin‐15, whereas claudin‐15‐mimicking K64W/K64M disturbed claudin‐10b integration into tight junctions. These data suggest that D55/D56 in the pore center but not E64/D65 of claudin‐15/‐10b directly attracts cations.